Clinical and Nutritional Assessment of Iron Deficiency Anemia in Children Under Two Years of Age - Abeer Abdel Rasool; Abdul Hammeed Hameed; Liqaa Alkhalidy (Medicinski glasnik, 2025)
Aim: To determine the frequency of iron deficiency anemia IDA, its causes, feeding behaviors, and preventive measures among children under the age of two. Methods: This cross-sectional study included 110 children presenting with IDA and compared them with 100 children with normochromic normocytic anemia as the comparison group. Results: Pallor was observed in all patients. Other symptoms included lethargy (83%), anorexia (65%), splenomegaly (27%), delayed milestones (25%), and heart murmurs (30%). The majority of affected children were aged 9-12 months and had weights below the 5th percentile. A strong correlation was found between feeding type and IDA, with highest prevalence in children not receiving milk-based diets. Hemoglobin and serum iron levels were significantly reduced in IDA patients. Conclusion: The study's findings suggest that factors like starting foods early or not getting enough iron from diet or formula milk can increase the risk of iron deficiency anemia (IDA) in children between 9 to 12 months old. This research highlights the role of nutritional strategies like appropriate weaning methods and iron supplementation, in averting IDAs and related health issues.
Keywords: Anemia; Infants; Iron Deficiency; Nutritional Deficiency.